Fate of river‐transported carbon in china: implications for carbon cycling in coastal ecosystems - Yang Gao (Taylor & Francis Group, 2017)
Rivers play an important role in carbon (C) exchange between terrestrial and oceanic water bodies and the atmosphere. The aim of this study was to systematically quantify fluxes in riverine C export and C exchange in the air–sea interface of marine ecosystems in China. Results show that annual C transport from rivers to coastal ecosystems in China can reach up to 64.35 TgC, which accounts for approximately 4.8%–8.1% of global C transport from river systems. In the Bohai Sea, particulate inorganic carbon is the main form of C influx, and it can reach up to 20.79 TgC/yr. Conversely, dissolved inorganic carbon is the main form of C influx into the East China Sea, and it can reach up to 10.52 TgC/yr, which is 42.6% of the total annual C imported into the East China Sea. China's marine ecosystems including the Yellow Sea, the Bohai Sea, the East China Sea, and the South China Sea can absorb 65.06 TgC/yr from the atmosphere.